2022
DOI: 10.3390/antiox11112116
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Lipid-Binding Proteins and Oxidative Stress in Neurodegenerative Disorders: A Focus on the Neuroprotective Effects of Nutraceutical Supplementation and Physical Exercise

Abstract: The human brain is primarily composed of lipids, and their homeostasis is crucial to carry on normal neuronal functions. In order to provide an adequate amount of lipid transport in and out of the central nervous system, organisms need a set of proteins able to bind them. Therefore, alterations in the structure or function of lipid-binding proteins negatively affect brain homeostasis, as well as increase inflammation and oxidative stress with the consequent risk of neurodegeneration. In this regard, lifestyle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 213 publications
1
6
0
Order By: Relevance
“…Next, biochemical determinations were performed on plasma and blood cell samples of the same subjects, to unveil specific signals related to oxidative stress and its epigenetic mechanisms of regulation. Plasma antioxidant activities toward hydroxyl and peroxyl radicals were significantly higher in ATL subjects as compared to SED ones, thus confirming our previous report 12 , 39 41 . Interestingly, TOSC values toward hydroxyl and peroxyl radicals were found to be directly related to NOx concentrations and blood flow post-heating and post- ischemia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Next, biochemical determinations were performed on plasma and blood cell samples of the same subjects, to unveil specific signals related to oxidative stress and its epigenetic mechanisms of regulation. Plasma antioxidant activities toward hydroxyl and peroxyl radicals were significantly higher in ATL subjects as compared to SED ones, thus confirming our previous report 12 , 39 41 . Interestingly, TOSC values toward hydroxyl and peroxyl radicals were found to be directly related to NOx concentrations and blood flow post-heating and post- ischemia.…”
Section: Discussionsupporting
confidence: 91%
“…It has been widely demonstrated that regular physical exercise (regular PA) is able to counteract inflammation and the negative effects of free radicals by inducing an adaptive response in endogenous antioxidant systems 11 . Generally, in athletes, levels of catalase (CAT) and glutathione peroxidase (GPx), are increased; in contrast, lipid peroxidation, which is considered the main oxidative marker, is considerably decreased 12 . Strenuous exercise was shown to cause immediate and delayed alterations in cardiovascular function 13 , 14 , however, the cardiovascular health benefits of acute and regular aerobic exercise are irrefutable 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Regular PA of moderate intensity has been recognized as a significant beneficial factor for health, reducing the risk of heart disease, stroke, hypertension, type 2 diabetes, colon cancer, breast cancer, osteoporosis, and even depression and anxiety ( Grande et al, 2019 ; Cunningham et al, 2020 ). In addition, PA positively affects neuronal functions, since it promotes neurotrophic factor production and synaptic plasticity as well as decreasing brain inflammation and oxidative stress ( Scarfò et al, 2002a ). However, a large part of the population is low-active or sedentary, engaging in levels of PA insufficient for health gain.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions involve sequential cleavage of the fatty acid chain, producing acetyl-CoA units. Acetyl-CoA is then further metabolized through the TCA cycle [ 56 , 57 ].…”
Section: Brain Energeticsmentioning
confidence: 99%